History of Geology:: Paleontological work of Lt. Col. C.C. Grant on the Silurian rocks of the Niagara Escarpment at Hamilton, Ontario - Hewitt, Roger (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1986)
Abstracts Lt. Col. Charles Coote Grant (1825-1914) organized the collection and donation of Silurian fossils at Hamilton and Grimsby in Ontario, over a continuous period from 1866 to 1914. He was a competent taxonomist and field geologist, who encouraged visits from professional geologists and wrote useful, if repetitive, papers in the 1889 to 1911 volumes of the Journal and Proceedings of the Hamilton Association. Grant anticipated a 20th-century trend in which field-oriented paleontologists become concerned with deductions from taphonomy and sedimentology.